Extraction and Identification of the Main Components of Cloves (Syzygium aromaticum L.) Oil Extract and its Antimicrobial Activity against Methicillin-resistant Staphylococcus aureus strain - U. Hashim, Mays; M.S. Ibrahim, Orooba (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Methicillin-resistant Staphylococcus aureus is widely recognized as a significant etiological agent responsible for infections around the world. One of the biggest problems in world health care is antibiotic resistance to the MRSA strain. The use of herbal medicines is one of the promising techniques for countering bacterial resistance to antibiotics. Objectives: The study is designed to investigate the chemical composition of clove oil extract and its in-vitro antibacterial activities against MRSA. Methods: The clove oil extract was obtained by using hydro-distillation by Clevenger apparatus. After that, phytochemical analysis was done to determine the secondary metabolites by Chromatography-Mass Spectrometry. In-vitro antimicrobial activity of clove oil extract against Methicillin-resistant Staphylococcus aureus was carried out by agar well diffusion method, the broth microdilution method, and in-vitro time-kill curve kinetic. Least significant difference –LSD test (Analysis of Variation-ANOVA) was used to significant compare between means of results in this study. Results: The results of this study revealed that the extraction percentage of the clove yielded 50%. The Chromatography-Mass Spectrometry results of the clove oil extract analysis showed that caryophyllen at 28.9%, Humulene at 21.6% and eugenol at 13.06% were the primary bioactive ingredients of the prepared extract. Furthermore, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of clove oil extract against Methicillin-resistant Staphylococcus aureus were found to be 2.5μg/ml and 5.0 µg/ml respectively. Time killing curve of 2xMICs and 4xMICs of clove extract achieved the highest significant bactericidal effect (P≤0.05) in comparison to other concentrations. Conclusions: The clove oil extract exhibited good in-vitro antibacterial properties and this can be attributed to the presence of phenolic compounds such as caryophyllene, humulene and eugenol.